Equações de predição para energia metabolizável da soja semi-integral extrusada para frangos de corte em diferentes idades - Meireles, Amanda Cecília de Sousa (2016)
The aim of this research was to determine the chemical composition and the energy values of the extruded semi-whole soybeans for broilers in different ages, elaborate prediction equations for estimating values of corrected apparent metabolizable energy (AMEn) of this feedstuff and evaluate the use of these equations on the feed formulation for broilers. Two experiments were conducted. In the first, three assays of metabolism were carried out using the traditional method of total excreta collection, to determine the energy values of soybean meal, extruded whole soybean and extruded semi-whole soybeans with four ethereal extract levels (12.2, 13.8, 17.7 and 18.8%). Laboratory tests were conducted to determine the chemical composition of the foods tested, which was utilized to prepare the prediction equations AMEn. The treatments consisted of the six feedstuffs and one reference ration. The birds were distributed on completely randomized experimental design, with seven treatments and six repetitions. In the first assay, it was used 336 broiler chicks males from 8 to 15 days of age, with eight animals by repetition. In the second assay, 252 broiler chicks males from 21 to 28 days of age were used, with six animals by repetition. In the third assay 168 broiler chicks males from 35 to 42 days of age were used, with four animals by repetition. The AMEn values (kcal/kg) based on the dry matter, determined with broiler chicks from 8 to 15, 21 to 28, 35 to 42 days of age were, respectively: 2,557, 2,588 and 2,653 for soybean meal; 3,757, 3,808 and 3,895 for extruded whole soybean; 3,295, 3,301 and 3,425 for extruded semi-whole soybeans 12.2% of ethereal extract; 3,444, 3,452 and 3,584 to extruded semi-whole soybeans 13.8% of ethereal extract; 3,528, 3,540 and 3,729 for extruded semi-whole soybeans 17.7% of ethereal extract; and, 3,660 3,650, and 3,849 for extruded semi-whole soybeans 18.8% of ethereal extract. After certain the AMEn values and composition of feedstuffs, prediction equations were obtained for each age of the birds, using the Stepwise procedure. For all ages studied, the common prediction equation was that which contained only the ethereal extract content of feedstuffs as a predictor of AMEn, which are: AMEn - 8 to 15 days of age - (Kcal/kg DM) = 2.459 +63,62 EE; AMEn - 21 to 28 days of age - (Kcal/kg DM) = 2.476 +63,82 EE; and AMEn - 35 to 42 days of age - (Kcal/kg DM) = 2.545 +68,15 EE. In the second experiment, we conducted a performance assay to evaluate the use of prediction equations for estimating the values of AMEn in formulating diets. 390 male day-old chicks were distributed in completely randomized design, with five treatments and six replications of 13 birds per experimental unit. The treatments consisted in: T1 = diet formulated with AMEn values (kcal/kg of NM) corn oil and soybean meal tabulated; T2 = diet formulated with AMEn values (kcal/kg of NM) tabulated corn and soybean meal and extruded semi-whole soybeans predicted at different ages; T3 = diet formulated with AMEn values (kcal/kg of NM) tabulated corn and extruded semi-whole soybeans predicted at different ages; T4 = diet formulated with AMEn (kcal/kg of NM) tabulated corn and soybean meal and extruded whole soybean predicted at different ages; T5 = diet formulated with AMEn (kcal/kg of NM) tabulated corn and extruded whole soybean predicted at different ages. The treatments did not affect significantly feed intake and chicken carcass characteristics. However, there was significant difference in weight gain and feed conversion, being these differences observed only between the birds fed with the tabulated AMEn values and that ones which were fed with the predicted values containing extruded whole soybeans, which showed better results. We conclude that the equations obtained can be used to estimate the AMEn value of extruded semi-whole soybeans depending on their level of fat.